2021
DOI: 10.1002/hed.26817
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck osteosarcomas: Analysis of treatment trends and survival outcomes in the United States (2004–2016)

Abstract: Background Head and neck osteosarcoma (HNOS) is a rare primary bone tumor with limited data to guide treatment approaches. Methods The NCDB was used to identify patients diagnosed with HNOS. Kaplan–Meier and Cox multivariate regression were used to examine the impact of each treatment on overall survival (OS). Results We identified 821 patients diagnosed with HNOS. Utilization of neoadjuvant chemotherapy + surgery increased from zero cases in 2004 to 24% of cases in 2016. Among surgically treated patients, 5‐y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The Memorial Sloan Kettering Cancer Center’s experience for head and neck osteosarcomas could not conclusively confirm improved tumor local control, decrease presence of distant metastases or improved disease-specific survival with the addition of neoadjuvant chemotherapy to conventional treatment. Furthermore, they suggest that the bone architecture of the tumor does not allow the mass to ‘shrink’ [ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Memorial Sloan Kettering Cancer Center’s experience for head and neck osteosarcomas could not conclusively confirm improved tumor local control, decrease presence of distant metastases or improved disease-specific survival with the addition of neoadjuvant chemotherapy to conventional treatment. Furthermore, they suggest that the bone architecture of the tumor does not allow the mass to ‘shrink’ [ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also very important is the study by Shim et al Shim et al analyzed data from 821 patients with COS from the National Cancer Database (NCDB) and compared 9 treatment cohorts with each other (surgery only, neoadjuvant chemotherapy + surgery, surgery+ adjuvant chemotherapy, neoadjuvant chemotherapy + surgery + adjuvant chemotherapy, surgery + adjuvant radiotherapy, surgery+ chemoradiation, chemoradiation, radiotherapy, and no treatment) (32). Shim et al failed to show an overall survival benefit with chemotherapy (neoadjuvant or adjuvant), radiotherapy, or a combination of these therapies (32).…”
Section: Impact Of Therapeutic Intervention On Survival Rates In Pati...mentioning
confidence: 99%
“…Interestingly, patients treated with neoadjuvant chemotherapy + surgery + adjuvant chemotherapy showed a survival advantage in the first 18 months compared to patients treated with surgery alone (95.8% vs. 78.5%). However, no long-term survival benefit could be achieved with chemotherapy or radiotherapy (32).…”
Section: Impact Of Therapeutic Intervention On Survival Rates In Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…
Rs e e p a g e 4 0 2 0 -4 0 2 1 Comment to: "Head and neck osteosarcomas: An analysis of treatment trends and survival outcomes in the United States (2004States ( -2016"We read, with great enthusiasm, the article by Shim et al, reporting the survival analysis of 821 patients diagnosed with head and neck osteosarcomas (HNOSs) from the National Cancer Database. 1 We would like to acknowledge the authors for this effort, which reflects the conflicting results regarding the benefits of neoadjuvant chemotherapy (neoCT). The authors concluded that "short-term survival improvement in patients receiving both neoadjuvant and adjuvant chemotherapy displays promise."
…”
mentioning
confidence: 99%